THE INFLUENCE OF E-COMMERCE, PRODUCT QUALITY AND BUYING INTEREST ON SALES LEVELS ON ENZO STONE - Marcella (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2022)
E-Commerce, product quality and buying interest are things that affect the level of sales at Enzo Stone. Good product quality is the expectation of all consumers. Enzo Stone has a target market for consumers who have an interest in buying natural stone. The use of e-commerce and Good product quality will help the level of sales in Enzo Stone. This study aims to determine the influence of e-commerce, product quality and buying interest on sales levels and using quantitative research methods by taking samples is by collecting samples in the form of kuesione on the goggle form which will be carried out when consumers come to Enzo Stone to buy goods. The population to be used is 100 samples taken from consumers who have purchased goods at Enzo Stone.Several regression research test liners are used as analytical tools to find out how they affect between indentent and dependent variables. The results of this study show that E-Commerce, Product quality and Buying Interest have a significant effect on the Level of Sales on Enzo Stone. R Square's result after conducting the study was 11.2%.